Exploring faculty members and medical sciences students’ experiences of E-learning during the COVID-19 pandemic - Zahra Borzabadi Farahani; Nazi Nejat; Ali Jadidi (International Journal of Africa Nursing Sciences)
Background: The present study was conducted to explain the experiences of using E-learning by the faculty members and the students during the COVID-19 pandemic. Method: A qualitative approach involving face to face interviews conducted in Arak University of Medical Sciences. Participants were faculty members (n = 8) and students (n = 10) who had the experience of E-learning during the COVID-19 pandemic. All interviews were recorded and transcribed verbatim… The data were coded using MaxQDA software and analyzed using content analysis. Results: Data analysis led to the generation of two main themes (Attitudes towards E-learning and strategies to improve E-learning quality with a number of categories and sub-categories identified in each: The advantages of virtual education Complementary approach(Saving time and money, People gathering, Access to content archive, Higher student engagement in education, Sharing educational content, Higher student satisfaction, Being appropriate to educational plan), The disadvantages of virtual education(The chances of disconnection, Inadequate interaction, E-learning is not appropriate for every course, Poor learning, Insufficient preparation, increased educational workload), Developing equipment (Developing proper infrastructure, Using multimedia approaches), Enhancing individual skills (Establishing interaction between faculty members and students in E-learning, Promoting evaluation methods, Providing efficient education, Blended learning Conclusions). Conclusion: E-learning cannot completely replace in-person education, but it can be used as a helpful and effective complementary approach to traditional education.